Perilaku Pengelolaan Keuangan Penggemar Produk Kolaborasi di Kalangan Mahasiswa: Pengaruh Financial Literacy, Lifestyle, Self-Control, dan Sikap Keuangan - Amelia Sukma Rosilawati; Melati Oktafiyani; Ririh Dian Pratiwi; Entot Suhartono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to evaluate the impact of financial literacy, lifestyle, self-control, and financial attitudes on the financial management practices of students at the Faculty of Economics and Business, Dian Nuswantoro University Semarang, particularly those involved in the purchase of collaborative products. The type of research conducted is quantitative research utilising primary data. The sampling process was conducted using the purposive sampling method. The population that is the subject of the research is active students in the Faculty of Economics and Business at Dian Nuswantoro University, totalling 2820 students. The total sample used was 338 students who had purchased or used collaborative products. The analysis method applied is multiple linear regression. The results of the data analysis show that financial literacy, lifestyle, self-control, and financial attitudes have a significant influence on students financial management. the obtained coefficient of determination value is 0,975 or 97,5 percent of financial management is influenced by financial literacy, lifestyle, self-control, and financial attitudes, while the remaining 2,5% variation is influenced by other variables not included in this study.